LFSR characteristic polynomial and phase shifter computation for two-dimensional test set generation (2017)
In built-in two-dimensional deterministic test pattern generation, a Linear Feedback Shift Register (LFSR) extended by phase shifters (PS) is commonly used for generating the test patterns. The specific LFSR/PS structure is currently chosen a-priori without regard to the actual test set. In this paper, we present a method to design the LFSR/PS structure based on the particular test set that we are given. Comparative experimental results show that the methodology can attain 100% coverage which cannot be achieved with current approaches. © 2017 IEEE.